2021
DOI: 10.3390/su13095043
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Teachers in Training on Water Issues and Their Relationship to the SDGs

Abstract: Water conservation is essential for any activity, as well as for the survival of both human and other living beings. It is commonly associated with access to clean water and sanitation, or even to unsustainable production and consumption, or sustainable cities and communities. However, there is increasing awareness of emerging issues related to water resources and their impact or relationship with other issues, such as climate change, access to food, health and well-being, or biodiversity (marine and terrestri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Therefore, universities wanting to adopt a greening strategy for campus life need to focus on developing awareness campaigns, which, in accordance with the findings of other studies [10,13,50,51,68,78], is crucial to the success of implementing sustainable consumption habits. Universities alone cannot implement extensive greening measures without coordinating their efforts with the utility services providers (water services, waste services, etc.)…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, universities wanting to adopt a greening strategy for campus life need to focus on developing awareness campaigns, which, in accordance with the findings of other studies [10,13,50,51,68,78], is crucial to the success of implementing sustainable consumption habits. Universities alone cannot implement extensive greening measures without coordinating their efforts with the utility services providers (water services, waste services, etc.)…”
Section: Discussionsupporting
confidence: 67%
“…Narrowing down the investigation to the students' showering routines, British researchers highlighted the impact that administrative measures and persuasive campaigns had on the water consumption in Bristol [50], but the specificity of the local context makes it difficult to replicate the research in a different cultural and administrative context. The gap in researching students' awareness of their water consumption habits, their attitudes toward saving water, or the issue of water management was highlighted in the scientific literature [51].…”
Section: Water Consumptionmentioning
confidence: 99%
“…After four evaluation rounds, those questions that did not score 80% as adequate or totally adequate in content validity were also eliminated. In this way, we were able to determine the coherence, adequacy, and consistency of the questions in addition to their content validity [46]. Thus, out of a total of 42 initial questions, our final interview ended up with 36 questions.…”
Section: Instrumentmentioning
confidence: 99%
“…First, teachers may not wish to incorporate such a topic in their classrooms. Ruiz-Garzón et al (2021) analyzed student teachers' perception of water resources and concluded that teachers realized people's unsustainable habits could negatively impact water resources and raised there is a need for raising social awareness. In other studies, scholars (Berglund and Gericke, 2016;Sinakou et al, 2019;Eli et al, 2020) suggested that teachers generally lack interest in implementing sustainability topics like water resources in their classrooms if these are not explicitly needed in their disciplines.…”
Section: Literature Reviewmentioning
confidence: 99%